PENGARUH E-COMMERCE, LITERASI KEUANGAN, DAN LITERASI DIGITAL TERHADAP PERILAKU KONSUMTIF MAHASISWA - Alfiyansyah, M. Arfi; Alamsyah, Sakti; Tanjung, Hendra (LPPM Universitas Bina Bangsa, 2024)
This study aims to examine whether there is an influence of e-commerece, financial literacy, digital literacy on consumtive behaviour. The population in this study were active accounting students of Muhamadiyah University The number of samples in this study were 77 respondents. The sampling technique uses simple random sampling method. The research method used is quantitative with primary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 27. The results of this study provide evidence that partially the e-commerce variable has a positive effect on consumptive behavior, while the financial literacy and digital literacy variables have a negative effect on consumptive behavior. Simultaneously e-commerce variables, financial literacy and digital literacy have a significant effect on consumptive behavior